(untitled) (Revista Contexto & Educação, 2026)
A large city, referred to in this article as Cidade Modelo, with a population growth of 14.1% (2010-2020), faces a shortage of school places in its outskirts, aggravated by the closure of schools in central areas. This study analyzed the impacts of this closure, considering the unequal distribution of educational infrastructure, especially in regions with popular multi-residential areas. The qualitative and exploratory research reveals that, while central schools were closed due to the drop in enrollment, the outskirts, such as neighborhoods with popular multi-residential areas, face overcrowding and a shortage of educational infrastructure. Closing without redistribution of resources increases inequalities, as in the case of School B, integrated with another school unit without adequate planning. The municipalization of institutions such as School D and School G also eliminated high school in these areas. It was observed that closed schools were reused as community or cultural centers to meet local demands. The study concludes that the integration between educational and urban policies is crucial to guarantee equitable access to education and sustainable development, emphasizing the importance of coordinated actions between education and urban planning to guarantee the provision of quality education in all regions of Cidade Modelo.